Documentary, performance and risk - Lyons, James 1972- (Routledge/Taylor & Francis Group, 2020)
"Documentary, Performance and Risk explores how some of the most significant recent American feature documentaries use performance to dramatically animate major categories of risk. The fact that these documentaries do rely on such performance is revealing both in terms of trends in American feature documentary, and in relation to the currency of ideas about risk in contemporary Western societies. The book takes a detailed look at the performance of risk and demonstrates the rewards of close critical attention to formal composition and performance. Covering An Inconvenient Truth, Super Size Me, Capitalism: A Love Story and Jackass: The Movie, it explores how these high-profile films offer up compelling narratives and images of individuals 'acting on risk'. The films seek to both confront and control the contours of their environments in ways that reveal much about how a particular set of beliefs about risk and the individual have come to inform our lives. This wide-ranging analysis of feature documentary is ideal for scholars and postgraduate students studying documentary film, film and media studies"--
Description based on online resource; title from resource home page (Taylor & Francis, viewed February 28, 2020)
Keywords: Documentary films / United States / History and criticism; Risk perception / United States; Motion picture acting